Śivagrha (Prambanan Temple) as an Archetype of Hindu Theology in Nusantara (An Endeavor to Discover Hindu Theological Knowledge through Ancient Temple Heritage) - Ni Kadek Surpi (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Many scholars believe that the Hindu community in Nusantara worship Trimūrti (Brahmā, Visnu, and Śiva) equally. This opinion is shared among the experts. However, it is not prevalent within Hinduism. Hence, it contradicts the concept of Ista Devata (the glorification of one Devata among the others). This qualitative study examines Prambanan Temple as an Archetype of Hindu Theology in Nusantara. This study focusses on the structure of the Prambanan temple complex, which related to the concept of Hindu Nusantara Theology, the depiction of Hindu Nusantara Theology, and the special meaning of Prambanan Temple. Data analysis was carried out using an Ethnographic Content Analysis (ECA). This study concludes that Prambanan Temple is convincing as an Archetype of Hindu Theology, in two typologies. The typology of Nirguna Brahman lies in the concept where Prambanan is a place to worship Parabrahman, The Absolute, The Supreme God. Meanwhile, the typology of Saguna Brahman lies in the concept where Prambanan is a Śivagrha, The House of Lord Śiva, a place to worship Śiva as the Highest Gods. This typology of Saguna Brahman is the base of Śivaistik Theology. Prambanan temple construction uses the Vāstupurusamandala pattern, which made it as the grandest temple in Nusantara. Even though Śivagrha is popular as a temple complex to worship Tri Murti as equals, the fact which lies in temple structures as well as in the manuscript (prasasti) proves that it has a Śivaistik Concept, where Śiva is worshiped as the highest Devata (Parabrahman).